PENGARUH SISTEM INFORMASI DAN PENGAWASAN TERHADAPEFEKTIVITAS KERJAKARYAWAN PADA PT. ANEKATAMBANG PERSERO TBK - Sani Mawarni; Muhammad Rifhananda (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2020)
Company to be a production activity unit that managed economy sources to prepare goods and service for society as a mean to get profit and so that can satisfy society need. Problem Formulation: 1) What found information system influence towards employee work effectiveness in PT. Aneka Tambang Persero Tbk?; 2) What found supervision influence towards employee work effectiveness in PT. Aneka Tambang Persero Tbk?; 3) how big information system influence and supervision according to together towards employee work effectiveness in PT. Aneka Tambang Persero Tbk? Watchfulness Result: 1) Found positive influence and significant between information system towards employee work effectiveness in PT. Aneka Tambang Persero Tbk and indikator-indikator integration, input, mengorganisasi, decision making, dependability, produce, classification, need, criteria, mutual connected, output, information processing, arrangement, interacted and user. 2) Found positive influence and significant between supervision towards employee work effectiveness in PT. Aneka Tambang Persero Tbk and indikator-indikator co-ordinating, increase pegawasan, malar, intellectual, work result evaluation, guarantee indepedensi, supervise activity, memberika warning, decide work connection, character or character, existing law rule, work method, disagree with planning, effective and authority. 3) Found positive influence and significant between information system and supervision according to together towards employee work effectiveness in PT. Aneka Tambang Persero Tbk and indicator- indicator planning, composed well, divide task, carry out task with goodly, supporting tool, brainchild, task that accepted as according to skill, there uniformity, existence efefektivitas effective, ability, increase quality, good evaluation, agreement avoids deviation, coordination process and commitment.